2020
DOI: 10.22271/chemi.2020.v8.i5u.10508
|View full text |Cite
|
Sign up to set email alerts
|

Effect of soil applied paclobutrazol on chemical quality of Litchi (Litchi chinensis Sonn.) cv. rose scented

Abstract: Paclobutrazol is a plant growth retardant and triazole fungicide has been reported to be very effective for dwarfing a wide range of crops including litchi. It is a cell elongation and internode extension inhibitor that retards plant growth by inhibition of gibberellins biosynthesis. The effect of paclobutrazol at varying time intervals of litchi as soil drench application (1.00-4.00 g a.i. per meter canopy diameter) was investigated during 2016-18 in Pantnagar condition. The Chemical quality of litchi was sig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…Paclobutrazol was applied to the selected trees across two years, in 2016 and 2017, respectively. Rose Scented is a prominent variety of India and is extensively grown in this region (Pant et al, 2020).The fruits of this cultivar have distinct rose aroma (Menzel and Waite, 2005). The tuberculate pericarp has an attractive red color.…”
Section: Plant Materialsmentioning
confidence: 99%
“…Paclobutrazol was applied to the selected trees across two years, in 2016 and 2017, respectively. Rose Scented is a prominent variety of India and is extensively grown in this region (Pant et al, 2020).The fruits of this cultivar have distinct rose aroma (Menzel and Waite, 2005). The tuberculate pericarp has an attractive red color.…”
Section: Plant Materialsmentioning
confidence: 99%
“…After harvesting, the fruit turn brown within a couple of days due to loss of water from the pericarp. Panwar et al [1] reported that salicylic acid decreases respiration rate by the closure of stomata. Salicylic acid (SA) is a natural plant hormone and it acts as signaling molecule.…”
Section: Introductionmentioning
confidence: 99%